2016
DOI: 10.1097/md.0000000000002444
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Function, Exercise Capacity, and Echocardiography Finding of Pediatric Patients With Kawasaki Disease

Abstract: Coronary artery (CA) abnormalities influence exercise capacity (EC) of patients with Kawasaki disease (KD), and Z-score of CA is a well established method for detecting CA aneurysm. We studied the influence of KD on cardiopulmonary function and EC; meanwhile we analyzed echocardiographic findings of KD patients. We also assessed the correlation between CA Z-score and EC of KD patients to see if CA Z-score of KD patients could reflect EC during exercise.Sixty-three KD patients were recruited as KD group 1 from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…Scholars have discovered that although children with KD have lower rates of myocardial perfusion while they are exercising, their cardiopulmonary function and exercise load capacities do not significantly differ from those of healthy children [ 1 , 2 ]. However, some studies have reported that children with KD have lower weekly moderate-to-vigorous activity (MVPA) than healthy children and lower exercise self-efficacy evaluations [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have discovered that although children with KD have lower rates of myocardial perfusion while they are exercising, their cardiopulmonary function and exercise load capacities do not significantly differ from those of healthy children [ 1 , 2 ]. However, some studies have reported that children with KD have lower weekly moderate-to-vigorous activity (MVPA) than healthy children and lower exercise self-efficacy evaluations [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…While most studies report improvement of myocardial function with treatment, there is now growing evidence that ongoing myocardial abnormalities occur in the long term (24). It has recently been shown that children suffering from subclinical myocardial complications during acute KD display long-term cardiovascular complications, such as lower myocardial flow reserve and higher total coronary resistance (33)(34)(35). However, few studies have considered a potential link between myocarditis in childhood KD and long-term persistent damage to the myocardium, including myocardial remodeling and fibrosis (30,36).…”
Section: Introductionmentioning
confidence: 99%
“…Tuan et al reported KD patients with/without CALs in chronic stage might still have compromised coronary perfusion during exercise. 22 The correlation of the baPWV and VO 2 peak may partially explain their finding. 22 Regular measurement of baPWV is useful to evaluate the degree of early atherosclerosis and cardiac dysfunction in KD patients.…”
Section: Discussionmentioning
confidence: 91%
“…A previous study by Tuan et al showed that KD patients with/without CALs in chronic stage might still have compromised coronary perfusion during exercise, which was related to the Z score of the coronary artery. 22 The long-term effect of these subclinical vascular changes on cardiovascular function is still unclear and merits further evaluation. The purpose of this study is to examine the arterial stiffness using baPWV and exercise performance of KD patients in chronic stage.…”
Section: Introductionmentioning
confidence: 99%